The Power of accepting Cheese Stick with the Addition of Anchovy Flour (Stolephorus Sp) to Stunting Toddlers - Ramah, Desly Adha; Hendrayati, Hendrayati; Rochimiwati, Siti Nur (Media Gizi Pangan, 2019)
Nutrition problems in Indonesia are still a serious health problem, especially malnutrition and stunting. Efforts to improve these nutritional problems can be through improved consumption patterns. Protein intake is one of the way to improve nutrition. One of the improvements in protein intake can be through the addition of anchovy in the form of cheese stick snacks.This study aims to determine the acceptability of cheese stick with the addition of anchovy flour. This type of research is pre-experiment with post test group research design. Acceptability was assessed based on a hedonic test of 30 panelists. The best results will be given to consumer panelists, namely stunting toddlers.The results showed that the highest panelists' acceptability was against the cheese stick with the addition of 10% anchovy flour. Panelis liked 57% flavor aspect, 50% color aspect, 63% aroma aspect and 97% texture aspect. The results of the study on consumer panelists that received by a toddler with a good category of 56.67%. It is recommended in making cheese stick with the addition of anchovy flour using a concentration of 10% because it is very preferred from the aspect of taste, color, aroma, texture and preferred by consumers.